Effect of resilient lining of obturator bulbs on patients with maxillectomies (2016)
Statement of problem. Poly(methyl methacrylate) (PMMA) obturator bulbs are hard and nonresilient. The relief for these obturators limits the support available for the bulbs and may limit mastication on the side with the resection. Resilient liners may improve mastication by gaining greater support from closer contact with tissues within the defects. Purpose. The purpose of this crossover clinical trial was to compare masticatory function scores of individuals with maxillectomies rehabilitated by using all-PMMA and PMMA obturator bulbs lined with resilient silicone. Material and Methods. Twelve participants with maxillectomies were provided with 2 definitive obturator dentures after initial rehabilitation. One of the obturator dentures had a hollow obturator bulb in all-PMMA, while the other had a hollow-core PMMA with an outer layer of silicone-resilient liner. Participants wore each obturator for a 2-week period without washout. Masticatory function on the rehabilitated sides was assessed by using an adapted Sato questionnaire. Statistical analysis was performed by using paired t test results of mean masticatory function scores (a=.05). Results. Participants found 98.35% of the foodstuffs easy to masticate on the dentate sides. An average of 60.40% of the participants found the foodstuffs easy to masticate on the rehabilitated sides with the silicone-lined obturators. 18.35% of participants found the foodstuffs easy to masticate with the all-PMMA obturators (P<.05). Conclusions. Resilient lining of PMMA resin obturator bulbs significantly improved masticatory ability in rehabilitated areas of the mouth. (J Prosthet Dent 2016;-:---)